2009
DOI: 10.1038/nsmb.1636
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic histone-DNA interactions are not the major determinant of nucleosome positions in vivo

Abstract: We assess the role of intrinsic histone-DNA interactions by mapping nucleosomes assembled in vitro on genomic DNA. Nucleosomes strongly prefer yeast DNA over E. coli DNA, indicating that the yeast genome evolved to favor nucleosome formation. Many yeast promoter and terminator regions intrinsically disfavor nucleosome formation, and nucleosomes assembled in vitro display strong rotational positioning. Nucleosome arrays generated by the ACF assembly factor display fewer nucleosome-free regions, reduced rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
527
4
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(563 citation statements)
references
References 34 publications
27
527
4
5
Order By: Relevance
“…Altogether our results agree with the central conclusions of recent experimental in vitro and in vivo studies of nucleosome positioning in S. cerevisiae (Zhang et al 2009), which provide additional evidence that intrinsic histone-DNA interactions make only a modest contribution to the in vivo intragenic nucleosome positioning pattern, the major determinant being the statistical ordering mainly induced by the excluding NFRs located at gene extremities.…”
Section: Proof Onlysupporting
confidence: 81%
“…Altogether our results agree with the central conclusions of recent experimental in vitro and in vivo studies of nucleosome positioning in S. cerevisiae (Zhang et al 2009), which provide additional evidence that intrinsic histone-DNA interactions make only a modest contribution to the in vivo intragenic nucleosome positioning pattern, the major determinant being the statistical ordering mainly induced by the excluding NFRs located at gene extremities.…”
Section: Proof Onlysupporting
confidence: 81%
“…For instance, Kaplan et al (23) concluded from genome-scale nucleosome mapping that intrinsic nucleosome sequence preferences have a dominant role in determining nucleosome organization in vivo. Shortly after this study, Zhang et al (24) reported a similar study on in vivo and in vitro assembled yeast chromatin, but using a somewhat different methodology. They and others (24,25) concluded that intrinsic histone-DNA interactions are not the major determinant of nucleosome positioning, but rather of nucleosome occupancy.…”
mentioning
confidence: 95%
“…Shortly after this study, Zhang et al (24) reported a similar study on in vivo and in vitro assembled yeast chromatin, but using a somewhat different methodology. They and others (24,25) concluded that intrinsic histone-DNA interactions are not the major determinant of nucleosome positioning, but rather of nucleosome occupancy. Positioning and occupancy of nucleosomes are closely related concepts; nucleosome positioning is the distribution of individual nucleosomes along the DNA sequence and can be thought of in terms of a single reference point on the nucleosome, such as its dyad of symmetry (9,26).…”
mentioning
confidence: 95%
“…Although several studies demonstrated that the intrinsic nucleosome organization determines many aspects of the nucleosome organization in vivo Zhang et al 2009), much less is known about the effect of the intrinsic organization on transcription. Our results thus suggest that intrinsic nucleosome organization may be an important component of the mapping between DNA sequence and transcription, and that changes in the DNA-encoded nucleosome organization of promoters may be a key genetic mechanism by which promoter activity changes are tuned during evolution ).…”
Section: Conclusion and Discussionmentioning
confidence: 99%